Blood flow restriction training on physical parameters in elite male canoe athletes - Tosun, U.; MsC, B.; Angin, E.; Kirmizigil, B.; Yolcu, M. (Medicine, 2023)
Background To investigate the effect blood flow restriction (BFR) exercises on muscle size, strength and athletic performance in elite canoe athletes aged 18 to 25 years.